2021
DOI: 10.36290/vnl.2021.028
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of LDL-C calculation by Martin, Sampson and old Friedewald methods in real data and synthetic data set

Abstract: Oddelenie klinickej biochémie a hematológie, Psychiatrická nemocnica Michalovce, n. o., Michalovce 2 Klinická epidemiológia a bioštatistika, Košice Cieľ: LDL-cholesterol (LDL-C) je stanovovaný metódami, ktorých presnosť je významne ovplyvnená v rôznych klinických alebo analytických situáciách. Novo boli popísané dve výpočtové metódy stanovenia LDL-C, rovnica Martin a rovnica Sampson, ktorých vlastnosti porovnávame s Friedewaldovou rovnicou. Súbor a metódy: Vzájomné porovnávania LDL-C stanovené uvedenými 3 rovn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
(6 reference statements)
1
2
0
Order By: Relevance
“…The M equation had the second-best predictive effect on LDL-C concentration, with a good fit between the predicted and measured values. However, the error in estimated LDL-C concentration was often large, and mostly underestimated, which is consistent with the findings of Ertürk et al [ 14 ] The S equation showed a similar ability to accurately calculate LDL-C concentration as the M equation, [ 15 ] but with higher convenience and lower imprecision and goodness-of-fit than the M equation. The F equation was the simplest and most widely used, [ 16 ] but its accuracy and precision in calculating LDL-C concentration were not as good as the above equations.…”
Section: Discussionsupporting
confidence: 88%
“…The M equation had the second-best predictive effect on LDL-C concentration, with a good fit between the predicted and measured values. However, the error in estimated LDL-C concentration was often large, and mostly underestimated, which is consistent with the findings of Ertürk et al [ 14 ] The S equation showed a similar ability to accurately calculate LDL-C concentration as the M equation, [ 15 ] but with higher convenience and lower imprecision and goodness-of-fit than the M equation. The F equation was the simplest and most widely used, [ 16 ] but its accuracy and precision in calculating LDL-C concentration were not as good as the above equations.…”
Section: Discussionsupporting
confidence: 88%
“…However, the error in estimated LDL-C concentration was often large, and mostly underestimated, which is consistent with the ndings of Ertürk et al [13] . The S equation showed a similar ability to accurately calculate LDL-C concentration as the M equation [14] , but with higher convenience and lower imprecision and goodness-oft than the M equation. The F equation was the simplest and most widely used [15] , but its accuracy and precision in calculating LDL-C concentration were not as good as the above equations.…”
Section: Discussionmentioning
confidence: 92%
“…Two studies each were performed in the following populations; Korean [49,55], HIV positive [33,54], high cardiac risk [34,58 ▪▪ ], fasting participant [37,38], hyperlipidaemic [43 ▪▪ ,47], Turkish [40,60], adults [30 ▪▪ ][66] and in children [10,44]. One study each was performed in the following populations; patients with coronary artery disease [31], renal disease [48], Hungarians [31], patients from the National Health and Nutrition examination survey [36], Persian cohort study patients [39], patients with acute MI [41,44], cardiology patients [36,45 ▪▪ ], those treated with PCSK-9 inhibitors [27], South African [9 ▪ ], Italian [31], Nigerian [50], Croatian [32], Slovakian [51], Lebanese [52 ▪ ], machine learning comparison, [53], a specialized lipid cohort [59], patients with hypertriglyceridaemia [61] and patients that received alirocumab, placebo, ezetimibe or a statin [2 ▪▪ ]. These studies provide a wide range of comparisons for use of formulae in different patient groups.…”
Section: Methodsmentioning
confidence: 99%